2018
DOI: 10.1038/s41396-018-0261-3
|View full text |Cite
|
Sign up to set email alerts
|

Localized recombination drives diversification of killing spectra for phage-derived syringacins

Abstract: To better understand the potential for antagonistic interactions between members of the same bacterial species, we have surveyed bacteriocin killing activity across a diverse suite of strains of the phytopathogen Pseudomonas syringae. Our data demonstrate that killing activity from phage-derived bacteriocins of P. syringae (R-type syringacins) is widespread. Despite a high overall diversity of bacteriocin activity, strains can broadly be classified into five main killing types and two main sensitivity types. F… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(52 citation statements)
references
References 44 publications
(62 reference statements)
6
33
0
Order By: Relevance
“…Tailocin target specificity is defined by its receptor-binding proteins (RBPs): tail fibers, tail spikes, and tail tips [3]. Recent studies have indicated that the RBPs are modular: they naturally undergo localized recombination [4], and they can be swapped in and out manually to engineer target specificity [5][6][7][8]. Following recognition and binding, tailocins kill target cells with very high potency, with one to a few particles sufficient for killing a sensitive cell [5,[9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Tailocin target specificity is defined by its receptor-binding proteins (RBPs): tail fibers, tail spikes, and tail tips [3]. Recent studies have indicated that the RBPs are modular: they naturally undergo localized recombination [4], and they can be swapped in and out manually to engineer target specificity [5][6][7][8]. Following recognition and binding, tailocins kill target cells with very high potency, with one to a few particles sufficient for killing a sensitive cell [5,[9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…This likely reflects the different environmental niches that P. aeruginosa and P. syringae occupy. Intriguingly, diversification and expansion of the tailocin family in P. syringae is driven by localized recombination of tailocin genes like those encoding the tail fibers (Baltrus et al, 2019).…”
Section: Tailocinsmentioning
confidence: 99%
“…Similarly, for CLBs appropriate domain swapping could yield chimeric bacteriocins for which there is no immunity protein-based resistance in the targeted bacterial species (Akutsu et al, 1989). For tailocins, the exchange of tail fibers has already been shown to produce novel chimeras (Baltrus et al, 2019).…”
Section: Applications Of Bacteriocins and Future Perspectivesmentioning
confidence: 99%
“…A wide body of evidence shows that tailocin-producing strains are resistant to the tailocins they produce 5,13 , in a phenotype referred to as resistance to self-intoxication ( Fig. 3A, Fig.…”
Section: Disruption Of Genes Encoding Outer Membrane Lipid Asymmetry mentioning
confidence: 99%
“…Tailocin target specificity is defined by its receptor-binding proteins (RBPs): tail fibers, tail spikes and tail tips 4 . Recent studies have indicated that the RBPs are modular: they naturally undergo localized recombination 5 , and they can be swapped in and out manually to engineer target specificity [6][7][8][9] . Following recognition and binding, tailocins kill target cells with very high potency, with one to a few particles sufficient for killing a sensitive cell 6,10-12 .…”
Section: Introductionmentioning
confidence: 99%